1965
DOI: 10.1161/01.res.16.3.244
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cardiac Hypertrophy in Exercise and in Hypoxia

Abstract: A group of rats, including both sexes, was exercised on an electrically-driven treadmill at the rate of one mile per hour for two hours daily to a total of 60 hours. Another group, also including both sexes, was exposed to intermittent hypoxia for eight hours daily, six days per week, for four weeks at a barometric pressure of 303 mm Hg corresponding to a simulated altitude of approximately 24,000 feet (7,315 m). All these animals showed significant hypertrophy of both ventricles. Exercise produced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

1966
1966
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 18 publications
2
6
1
Order By: Relevance
“…When the primary stimulus is volume overload, however, the elevation in diastolic wall stress should be relatively greater per unit volume of tissue in the right ventricle because of its smaller total number of myocytes, less ventricular mass, and thinner wall. In contrast with the present findings in Wistar Kyoto rats, an approximately similar amount of hypertrophic growth in the right and left ventricular myocardium has been shown in albino rats subjected to the same kind of physical conditioning (Van Liere et al, 1965). On the other hand, both female and male Sprague-Dawley rats on a more moderate treadmill running program did not develop hypertrophy of either ventricle (Dowell et al, 1976a(Dowell et al, , 1976b.…”
Section: Discussioncontrasting
confidence: 86%
“…When the primary stimulus is volume overload, however, the elevation in diastolic wall stress should be relatively greater per unit volume of tissue in the right ventricle because of its smaller total number of myocytes, less ventricular mass, and thinner wall. In contrast with the present findings in Wistar Kyoto rats, an approximately similar amount of hypertrophic growth in the right and left ventricular myocardium has been shown in albino rats subjected to the same kind of physical conditioning (Van Liere et al, 1965). On the other hand, both female and male Sprague-Dawley rats on a more moderate treadmill running program did not develop hypertrophy of either ventricle (Dowell et al, 1976a(Dowell et al, , 1976b.…”
Section: Discussioncontrasting
confidence: 86%
“…Since this disagreement exists we would point out that many factors such as the sex, age, and health of the animals play a role in the genesis of hypoxia-in duced left ventricular hypertrophy. More over, in our experiments the rats under went a more severe and sustained degree of hypoxia than in previous studies [11,16,21,23]. Our data show a significant de gree of left ventricular hypertrophy in the posthypoxic rats.…”
Section: Discussionsupporting
confidence: 43%
“…However, a number of critical factors including increase in cardiac out put [21]: overload imposed to the left ven tricle by polycythemia [I]; deficiency of high energy phosphate [13] and/or circu lating factors [2,3] may account for the de velopment of the hypertrophic process in our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown that rats undergoing chronic running exercise-training develop increased left ventricular hypertrophy. Previous studies have shown that endurance exercisetraining increases the left ventricular wall thickness in rats (Liere et al 1965). Left ventricular hypertrophy can be explained by a marked increase in the systemic circulation during the exercise, i.e.…”
Section: Discussionmentioning
confidence: 96%